Enhanced Cloud Computing Security Based on Single to Multi Cloud Systems - Ojha, Pranav (Journal of Research in Science and Engineering, 2024)
Cloud computing has increased rapidly in many organizations and then it's utilized. Cloud computing provides safe data. Cloud computing provides many advantages in terms of low cost and accessibility of data. Ensuring the security of cloud computing is a major factor in the cloud computing environment, as users often store sensitive information with cloud storage providers but these providers may be untrusted. Dealing with "single cloud" providers is predicted to become less popular with customers due to risks of service availability failure and the possibility of malicious insiders in the single cloud. A movement towards "multi - clouds", or in other words, "inter clouds" or "cloud - of - clouds" has emerged recently. We propose the recent research related to single and multi - cloud security and address possible solutions. It is found that the research into the use of multi - cloud providers to maintain security has received less attention from the research community than the use of single clouds. This work aims to promote the use of multi - clouds due to their ability to reduce security risks that affect the cloud computing user. We proposed the AES algorithm can explore the cloud sharing to multiple clouds. This algorithm protects secure to personal information, financial records, and other confidential records. The system is highly effective in accuracy.